Restructuring relations : indigenous self-determination, governance, and gender - Kuokkanen, Rauna (Oxford University Press, 2019)
This book interrogates normative conceptions of Indigenous self-determination and the structures of Indigenous self-government institutions, arguing that Indigenous self-determination is not achievable without restructuring all relations of domination beyond that with the state; nor can it be secured in the absence of gender justice. It demonstrates that the current rights discourse and focus on Indigenous–state relations is limited in scope and fails to convey the full meaning of self-determination for Indigenous peoples. Besides settler colonialism and neoliberal capitalism, relations of domination include racism, sexism, homophobia, misogyny, and gender violence, including violence against women, queer, trans and gender-nonconforming persons, and structural violence. Drawing on extensive participant interviews in Canada, Greenland, and Scandinavia, this book theorizes Indigenous self-determination as a foundational value, informed by the norm of integrity. This norm has two interrelated dimensions: bodily integrity and integrity of the land, both of which are a sine qua non for Indigenous gender justice. Conceptualizing self-determination as a foundational value seeks to restructure all relations of domination, including the hierarchical relation between self-determination and gender created and maintained by international law, Indigenous political discourse, and Indigenous institutions. The book argues that the persistent separation of issues between self-determination/self-government and gender/social is a major obstacle in implementing, realizing, and exercising Indigenous self-determination. Restructuring relations of domination further entails examining the gender regimes present in existing Indigenous self-government institutions, interrogating the relationship between Indigenous self-determination and gender violence, and considering future visions of Indigenous self-determination, including rematriation of Indigenous governance and an independent statehood.
Keywords: Indigenous peoples : Government relations; Indigenous peoples : Politics and government; Feminist theory; Self-determination, National; alkuperäiskansat; perusoikeudet; itsehallinto; suvereniteetti; poliittiset instituutiot; itsemäärääminen; kansainvälinen oikeus; sosiaaliset suhteet; naisen asema; rakenteellinen väkivalta; naiset; feministinen teoria